Learning Phonology from Surface Distributions, Considering Dutch and English Vowel Duration. Issue 3 (3rd July 2019) - Swingley, Daniel
ABSTRACT: In learning language, children must discover how to interpret the linguistic significance of phonetic variation. On some accounts, receptive phonology is grounded in perceptual learning of phonetic categories from phonetic distributions drawn over the infant's sample of speech. On other accounts, receptive phonology is instead based on phonetic generalizations over the words in the lexicon. Tests of these hypotheses have been rare and indirect, usually making use of idealized estimates of phonetic variation. Here we evaluated these hypotheses, using as our test case English and Dutch toddlers' different interpretation of the lexical significance of vowel duration. Analysis of thousands of vowels of one Dutch and three English mothers' speech suggests that children's language-specific differences in interpretation of vowel duration are likely due to detection of lexically specific patterns, rather than bimodality in raw phonetic distributions.